적외선 방사가열법에 의한 Ti(C,N)-Mo2C-Ni 서멧의 내열충격성 평가 - 신순기; Soon Gi Shin (대한금속·재료학회지, 48(9), 2010)
An attempt was made to evaluate the thermal shock resistance of Ti(C,N)-Mo2C-Ni cermets by the infrared radiation heating method. The method uses a thin circular disk that is heated by an infrared ray at the central area with a constant heat flux. The technique makes it possible to evaluate the thermal shock strength (Tss) and thermal shock fracture toughness (Tsf) directly from the electric powder charge and the time of fracture despite the fact that Tss and Tsf consist of the thermal properties of the material tested. Tsf could be measured for specimens with an edge notch, while Tss could not be measured for the specimens without the notch. It was thought, however, that Tsf might depend on the radius of curvature of the edge notch. Using the data of Tsf, Tss was calculated from the consideration of stress concentration. As a result, it was considered that Tss could be applied to the evaluation of the thermal shock resistance of cermet, and the thermal shock resistance of Ti(C,N)-Mo2C-Ni cermets increased with an increase in the content of nitrogen and Ni.